Cybervictimization across relationships and contexts: a focus on victimization within dating relationships during early adolescence - Garthe, Rachel C. (Violence and victims, 2025)
Cybervictimization can occur within friendships, within dating, peer, or family relationships, between strangers, or it can be anonymously perpetrated. However, research examining cybervictimization across these various relationships and contexts—especially the cybervictimization that can occur within dating relationships during early adolescence—remains underdeveloped. The current study examined cybervictimization among a sample of early adolescents in middle school. We also examined if cybervictimization (across relationships and contexts) and traditional forms of victimization (i.e., peer and dating violence that happen offline) were associated with an increased risk for cybervictimization from a dating partner. Participants included 554 early adolescents (49% female) in the sixth and seventh grades at a public middle school in the Midwestern United States during the fall of 2019. Participants were racially diverse (33% African American or Black, 26% White, 15% Hispanic or Latinx, 19% multiracial) and half of the sample had started dating (n = 230). Approximately 59.2% of the sample experienced at least one form of cybervictimization in the past year. Adolescents experienced cybervictimization from friends (39.9%), someone at school (24.4%), a stranger (22.6%), a family member (25.6%), or another perpetrator (20.8%). About 72% of adolescents who started dating experienced at least one form of cybervictimization and about one in four experienced cybervictimization from a dating partner (22.6%). Experiencing offline dating violence and cybervictimization from friends was associated with cybervictimization from a dating partner. Implications are discussed, including the importance of focusing on cybervictimization and dating violence prevention among early adolescents.